Long-term results of irrigated bipolar radiofrequency ablation in patients with recurrent arrhythmia after failed unipolar ablation - Baszko, Artur (Medicine (Baltimore), 2020)
INTRODUCTION: The RF ablation of ventricular tachycardia (VT) or atrial flutter (AFl) can be unsuccessful due to lack of lesion transmurality. Bipolar ablation (BA) is more successful than unipolar ablation (UA). The purpose of our study was to investigate the long-term effect of BA ablation in patients after failed UA. METHODS: Patients with septal VT (5) or AFL (2) after 2 to 5 unsuccessful UA were prospectively analysed after BA. All patients presented with heart failure or had ICD interventions. RESULTS: BA was successful in 5 patients (1 failure each in the AFL and VT group). The follow-up duration was 10 to 26 months. In AFL group, BA was successful in 1 patient, unidirectional cavotricuspid block in was achieved in the other patient. All patients were asymptomatic for 12 months, but 1 had atrial fibrillation and the other had AFL reablation 19 months after BA. In VT group, all patients had several forms of septal VT. BA was successful in 4 patients. In 2 patients with high septal VT BA resulted in complete atrioventricular block. During follow-up, 1 patient had VT recurrence 26 months after BA and died after an unsuccessful reablation. Three patients had VT recurrences of different morphologies, which required reablation (UA in 2 and alcohol septal ablation in the other patient). CONCLUSION: BA was successful in patients with AFL and septal VT resistant to standard ablation. Relapses of clinical arrhythmia are rare; however, long-term follow-up is complicated by recurrences of different arrhythmias related to complex arrhythmogenic substrate